Rh(II)-catalyzed intramolecular N-H insertion of D-glucose-derived delta-amino alpha-diazo beta-ketoester: Synthesis of pyrrolidine iminosugars - Vyavahare, Vinod P.; Chattopadhyay, Subrata; Puranik, Vedavati G.; Dhavale, Dilip D. (Synlett, 2007)
The rhodium acetate catalyzed reaction of D-glucose-derived delta-amino alpha-diazo beta-ketoester allows a stereoselective beta-facial intramolecular N-H insertion reaction that leads to formation of the bicyclic pyrrolidinone ring skeleton in high yield. The sugar-substituted pyrrolidinone thus obtained was elaborated to allow the synthesis of promising glycosidase inhibitors, namely, 2,5-dideoxy2,5-imino-L-glycero-alpha-D-galactoheptitol and 2,5-dideoxy-2,5-imino-D-galactitol.
Keywords: alkaloids; azasugars; carbohydrates; N-H insertion; Pyrrolidines; rhodium carbenoid

Synthesis of 1-deoxy-1-hydroxymethyl- and 1-deoxy-1-epi-hydroxymethyl castanospermine as new potential immunomodulating agents - Vyavahare, Vinod P.; Chakraborty, Chaitali; Maity, Biswanath; Chattopadhyay, Subrata; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Medicinal Chemsitry, 2007)
Two new C-1 epimeric hydroxymethyl castanospermine congeners 2a and 2b, synthesized by stereocon trolled intramolecular double reductive amination Of D-glucose derived beta-keto ester as a key step, showed impressive immuno-potentiating property. The bioactivity was mediated through up-regulation of T-H1/T-H2 cytokine ratio. The finding suggested that immunmodulatory activity of polyhydroxylated indolizidine alkaloids can be tuned by minor structural/stereochemical alterations.

Synthesis of five and six membered aminocyclitols: stereoselective michael and henry reaction approach with D-glucose derived alpha,beta-unsaturated ester - Chakraborty, Chaitali; Vyavahare, Vinod P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2008)
The stereoselective intermolecular Michael addition of nitromethane to D-glucose derived alpha,beta-unSaturated ester 7 afforded L-ido-configurated nitroester 8 as the only product that on reduction of the ester functionality, cleavage of 1,2-acetonide and the intramolecular Henry reaction afforded exclusively muco-nitroinositol 9. While reduction of the ester functionality in 8, deprotection of 1,2-acetonide, oxidative cleavage with NaIO(4) and the intrarnolecular Henry reaction afforded nitrocyclopentitol 13. Nitrocyclitols 9 and 13 were converted to the hydroxyethyl substituted aminocyclohexitol 5 and aminocyclopentitol 6, respectively. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: aminocyclitols; carbohydrates; Henry reaction; Michael addition; nitroinositol